pengaruh metode eksperimen terhadap pengenalan warna pada anak usia dini - mulyadi, asri tia; wulansuci, ghina (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
One aspect of cognitive development that can be developed by children is by the introduction of color in early childhood, for it is necessary to do learning through learning methods that can improve the development of color recognition capabilities. Because cognitive development must be mastered by children to recognize colors related to sharpening the ability of imagination, develop intelligence and mindset in children. One method that can be done to introduce color is through an experimental method to determine the ability of children to explain the process of something that has been tried, provide a learning experience for students about the process of something happening, and bring a high enthusiasm to children. This study used a quasi-experimental method with nonequivalent control group design research design using two classes consisting of A1 experimental class and A2 control class at Al-Falah Kindergarten. Based on the results of the study, it was found that the average gain of the experimental class was 22.30 while the average gain value of the control class was 1.69, which means that the effect of color recognition on the experimental class children after treatment was increased compared to the untreated control class. Therefore, this research is recommended for early childhood educators that the experimental method can influence color recognition for early childhood.